Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter 1 - Equations and Inequalities - 1.6 Other Types of Equations and Applications - 1.6 Exercises: 27

Answer

The equation has no solution.

Work Step by Step

$\dfrac{x}{x-1}-\dfrac{1}{x+1}=\dfrac{2}{x^{2}-1}$ Factor the denominator of the fraction on the right side of the equation: $\dfrac{x}{x-1}-\dfrac{1}{x+1}=\dfrac{2}{(x-1)(x+1)}$ Multiply the whole equation by $(x-1)(x+1)$: $(x-1)(x+1)\Big[\dfrac{x}{x-1}-\dfrac{1}{x+1}=\dfrac{2}{(x-1)(x+1)}\Big]$ $x(x+1)-(x-1)=2$ Evaluate the indicated operations: $x^{2}+x-x+1=2$ Take $2$ to the left side and simplify: $x^{2}+x-x+1-2=0$ $x^{2}-1=0$ Solve by factoring: $(x-1)(x+1)=0$ Set both factors equal to $0$ and solve each individual equation for $x$: $x-1=0$ $x=1$ $x+1=0$ $x=-1$ The original equation is undefined for $x=1$ and $x=-1$, so it has no solution.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.